The moralist of the Empire - França, Jean Marcel Carvalho [UNESP]; Ferreira, Ricardo Alexandre [UNESP] (FapUNIFESP (SciELO), 2022)
The article addresses a relatively discreet character, although a very present one in the process of Independence and construction of independent Brazil: Mariano José Pereira da Fonseca, the marquis of Maricá. It is our goal, above all, to analyze the life and trajectory of the Marquis, as well as the general aspects of his moral reflections, and the place that his single published work occupied in Brazilian society. That being the Coleção completa das Máximas, pensamentos e reflexões do marquês de Maricá, a moral guide that, as we will try to demonstrate, was well regarded among the public during the first half of the 19th century - from readers of newspapers, books and magazines to purchasers of leaflets enriched with the Marquis' maxims -, having an undisputable role in its formation.
El moralista del Imperio
O moralista do Império
Keywords: catholicism; independent Brazil; marquis of Maricá; maxims